Pemberdayaan Petani Wanita di Jambula berbasis Pertanian Berkelanjutan oleh PT Pertamina Patra Niaga Fuel Terminal Ternate - Simanjuntak, Citra Lesmana; Watratan, Leonardus; Iqbal, Muhammad (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to determine the implementation of community empowerment through  the Corporate Social Responsibility (CSR) program of PT Pertamina Patra Niaga Fuel Terminal Ternate in the Intan Persala Farmer Women Group in Jambula Village, with a focus on the implementation of sustainable agriculture. The research method uses a participatory approach that actively involves members of the Women Farmer Group (KWT) in planning, implementing, and evaluating programs through qualitative data collection techniques such as interviews, observations, and Focus Group Discussions (FGD). The results of the study show an increase in the technical and socio-economic capacity of KWT members in implementing environmentally friendly agricultural practices, followed by the adoption of organic fertilizer technology and agroecological practices, as well as increasing economic independence and women's involvement in agricultural decision-making. The positive impact of this empowerment can be seen in increasing productivity, preserving the environment, and increasing market access to organic products. This study makes an important contribution to the development of sustainable and inclusive community empowerment models in agriculture-based urban areas.